Developmental and mechanical roles of Reichert's membrane in mouse embryos. (5th December 2022) - Matsuo, Isao; Kimura-Yoshida, Chiharu; Ueda, Yoko
Abstract : Embryonic development and growth in placental mammals proceeds in utero with the support of exchanges of gases, nutrients and waste products between maternal tissues and offspring. Murine embryos are surrounded by several extraembryonic membranes, parietal and visceral yolk sacs, and amnion in the uterus. Notably, the parietal yolk sac is the most outer membrane, consists of three layers, trophoblasts and parietal endoderm (PaE) cells, and is separated by a thick basal lamina termed Reichert's membrane (RM). RM is composed of extracellular matrix (ECM) initially formed as the basement membrane of the trophectoderm of pre-implanted embryos and followed by the heavy deposition of ECM mainly produced in PaE cells of post-implanted embryos. In addition to the physiological roles of RM, such as gas and nutrient exchange, it also plays a crucial role in cushioning and dispersing intrauterine pressures exerted on embryos for normal egg-cylinder morphogenesis. Mechanistically, such intrauterine pressures generated by uterine smooth muscle contractions appear to be involved in the elongation of the egg-cylinder shape, along with primary axis formation, as an important biomechanical element in utero . This review focuses on our current views of the roles of RM in properly buffering intrauterine mechanical forces for mouse egg-cylinder morphogenesis. This article is part of the theme issue 'Extraembryonic tissues: exploring concepts, definitions and functions across the animal kingdom'.